2014
DOI: 10.1097/01.asw.0000451891.87020.69
|View full text |Cite
|
Sign up to set email alerts
|

The Use of PriMatrix, a Fetal Bovine Acellular Dermal Matrix, in Healing Chronic Diabetic Foot Ulcers

Abstract: The results of this multicenter prospective study demonstrate that the use of PriMatrix integrated with standard-of-care therapy is a successful treatment regimen to heal DFUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…222,223 Currently available nonhuman ECM products with clinical data to support their efficacy include porcine-derived small intestinal submucosa, porcine urinary bladder matrix, bovine dermis, equine pericardium, and sheep (ovine) bladder. [224][225][226][227][228][229][230][231][232][233] Another matrix dressing (Hyalomatrix Ò ; Anika Therapeutics, Inc., Bedford, MA) comprising primarily hyaluronan, one of the main constituents of ECM, has also been studied in Europe as a dermal substitute for use in burns, VLUs, and DFUs. [234][235][236][237] Integra Ò bilayer wound matrix (Integra LifeSciences, Plainsboro, NJ) is a dermal regeneration template in this category (bovine collagen, glycosaminoglycans, and silicone layer) that has primarily been used in burns for a number of years, but is being more frequently used in lower extremity chronic wounds and foot ulcers.…”
Section: Biological and Bioengineered Therapiesmentioning
confidence: 99%
“…222,223 Currently available nonhuman ECM products with clinical data to support their efficacy include porcine-derived small intestinal submucosa, porcine urinary bladder matrix, bovine dermis, equine pericardium, and sheep (ovine) bladder. [224][225][226][227][228][229][230][231][232][233] Another matrix dressing (Hyalomatrix Ò ; Anika Therapeutics, Inc., Bedford, MA) comprising primarily hyaluronan, one of the main constituents of ECM, has also been studied in Europe as a dermal substitute for use in burns, VLUs, and DFUs. [234][235][236][237] Integra Ò bilayer wound matrix (Integra LifeSciences, Plainsboro, NJ) is a dermal regeneration template in this category (bovine collagen, glycosaminoglycans, and silicone layer) that has primarily been used in burns for a number of years, but is being more frequently used in lower extremity chronic wounds and foot ulcers.…”
Section: Biological and Bioengineered Therapiesmentioning
confidence: 99%
“…The acellular collagen scaffold we utilized here (Primatrix, Integra) has been used clinically in prepared human wound beds to support granulation and revascularization of the wound bed before STSG (Kavros et al., 2014, Strong et al., 2016). Unsurprisingly, our results showed that addition of this particular scaffold at the time of grafting impeded graft take, since it may act as a barrier to revascularization of the STSG from the wound bed.…”
Section: Discussionmentioning
confidence: 99%
“…PriMatrix ® , Oasis ® , and TissueMend™ are other available collagen matrix-based skin substitutes, which also do not exhibit immunological rejection. PriMatrix ® is a fetal bovine dermal substitute comprising extracellular Type I and III collagen matrix scaffolds and used for the coverage of complex wounds to stimulate vascularization and dermal regeneration [ 122 , 158 , 159 ]. Oasis ® is an acellular dermal substitute fabricated from porcine small intestine [ 7 , 122 , 148 ].…”
Section: Approaches To Avoid Skin Immune Rejectionmentioning
confidence: 99%